Cultivo da mamona utilizando percolado de aterro sanitário como fonte hídrica e nutricional - Andrade Filho, Jerônimo (Universidade Federal Rural do Semi-Árido, 2016)
The rapid population growth associated with the increase of per capita consumption of goods, products and food have caused the increase in the production of urban solid waste and consequently the production of percolate. Therefore, treatment techniques or use of this liquid waste must be improved in order to minimize its environmental impact. This work was carried out on the premises of the Universidade Federal Rural do Semiárido campus of the in the city of Mossoro, RN in order to evaluate the effects of application of landfill leachate in the cultivation of Castor Bean (Ricinus communis L. cv. Energy).The experimental design adopted was randomized blocks in which we tested the application through irrigation of dilution percolate [T1 - water supply + mineral soil fertilization, T2 - 20% of percolate, T3 - 40% of percolate, T4 - 60% of percolated and T5 - 80% of percolated] with five treatments and four replications in a red-yellow eutrophic clay soil. In each portion, soil samples were collected at three depths (0.00 to 0.05, 0.05 to 0.15 and 0.15 at 0.30 m) with which was determined the chemical characteristics of the soil. Plant samples were collected to evaluate the growth characteristics at 30, 60, 90 and 120 DAS (Days After Sow), biomass production of the airy part at the end of the cycle, crop yield at 90 and 120 DAS, as well as content and characterization of seed oil at 120 DAS. The application of percolated dilutions in the soil significantly influenced the pH, Ca, Cu, Fe, Ni, Cd and Pb characteristics. The irrigated treatments with percolated dilutions showed no exchangeable sodium percentage values that indicate soil salinization, neither values of heavy metals that indicated contamination. Growth variables as plant height, stem diameter, number of leaves were influenced significantly by dilution, and the treatment T4 showed the best result. The plant biomass values were not affected by percolated dilutions. The crop yield was significantly influenced by dilution of percolated, and among the treatments that received dilutions, the one which performed better according to this variable was the treatment T2. In terms of oil content, the treatments that showed the best results were treatment T1 and treatment T4, with the values of 17.01 and 13.85%, respectively. The characteristics of oils of these two analyzed treatments present relative density, acid index, saponification index and fatty acids values suitable for biodiesel production. The fertigated castor bean tree cultivation with landfill leachate proved to be viable from the point of view of yield and growth as well as oil production as raw material for biodiesel production
Castor Bean cultivation using landfill percolated as water and nutritional source
Keywords: Resíduo líquido; Reuso; Sustentabilidade; Biodiesel; Liquid Waste; Reuse; Sustainability; Biodiesel; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO